Output eller outcome, hur styrs polisen? En kvalitativ textanalys av polisens styrdokument - Doll,Ellen; Ingelbratt,Tobias (2017)
New Public Management (NPM) is an approach to running public services which originates from the private sector, favouring ideas of competition, privatization, measurment of results etc. While there are benefits to this approach, it has also caused various problems within both the Swedish police and the public service in general. Thus, NPM in the public sector has been strongly criticized throughout the years. By 2015, the Swedish Police went through a massive reorganization, raising the question of whether the criticism has been considered. The purpose of this study is to identify whether there has been any change during this period of time in the way the Swedish Police prioritizes their activities from a NPM perspective. While NPM is a somewhat broad term, we are looking into specific aspects of NPM that are linked to the concepts of ’output’ and ’outcome’. The analysis is based on public documents extending over 2012, 2014 and 2015, issued by the Swedish government and the Swedish Police. The results of this study show that a change from ’output’ towards ’outcome’ has occured in the way the the police is governed. This change is particularly significant between 2014 and 2015
Keywords: New Public Management; NPM; Swedish Police; output; outcome.